2021
DOI: 10.3390/cancers13102300
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Protein Biomarkers Associated with Higher Ovarian Cancer Risk in BRCA1/2 Carriers

Abstract: Ovarian cancer (OC) is the most lethal gynecologic malignancy and in-time diagnosis is limited because of the absence of effective biomarkers. Germline BRCA1/2 genetic alterations are risk factors for hereditary OC; risk-reducing salpingo-oophorectomy (RRSO) is pursued for disease prevention. However, not all healthy carriers develop the disease. Therefore, identifying predictive markers in the BRCA1/2 carrier population could help improve the identification of candidates for preventive RRSO. In this study, pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…Our targeted MS assays showed that expressions of 18 out of 21 candidates showed statistically significant (P < 0.05) changes between HGSOC and HCs (Table 2), consistent with those from LC−DIA− MS/MS analysis. Some of the 18 biomarker candidates have previously been suggested as potential serum diagnostic biomarkers for OC, including C3, 32 MPO, 33 LBP, 34 CD14, 35 APOA1, 36 APOA4, 37 IGFBP2, 38 LRG1, 39 and THBS1, 40 while others, to the best of our knowledge, were identified as potential OC serum biomarkers for the first time in the current study. To evaluate diagnostic values of the 18 diagnostic biomarkers for HGSOC, we developed a multi-biomarker predictive model for discriminating between HGSOC and HCs in the validation cohort.…”
Section: Validation Of Potential Diagnostic Biomarkers For Hgsocmentioning
confidence: 64%
See 1 more Smart Citation
“…Our targeted MS assays showed that expressions of 18 out of 21 candidates showed statistically significant (P < 0.05) changes between HGSOC and HCs (Table 2), consistent with those from LC−DIA− MS/MS analysis. Some of the 18 biomarker candidates have previously been suggested as potential serum diagnostic biomarkers for OC, including C3, 32 MPO, 33 LBP, 34 CD14, 35 APOA1, 36 APOA4, 37 IGFBP2, 38 LRG1, 39 and THBS1, 40 while others, to the best of our knowledge, were identified as potential OC serum biomarkers for the first time in the current study. To evaluate diagnostic values of the 18 diagnostic biomarkers for HGSOC, we developed a multi-biomarker predictive model for discriminating between HGSOC and HCs in the validation cohort.…”
Section: Validation Of Potential Diagnostic Biomarkers For Hgsocmentioning
confidence: 64%
“…For the dual online LC system, two solid-phase extraction (SPE) columns (150 μm × 3 cm) and two analytical columns (75 μm × 150 cm) were manufactured in-house packed using Jupiter C18 materials (3 μm, 300 Å, Phenomenex) and were heated at 60 °C. 12 The serum peptides (25,40, or 50 μg) from each pooled sample group were injected and separated on the mid-pH column for the online first dimensional separation (Table S2). A mid-pH solvent A (10 mM TEAB in water, pH 7.5) and a mid-pH solvent B (10 mM TEAB in 99% ACN, pH 7.5) were used to generate a gradient (1−50% solvent B for 120 min at a flow rate of 1 μL/min).…”
Section: Comprehensive Serum Proteome Profiling Experiments For Serum...mentioning
confidence: 99%
“…To date LC-MS-based quantitative proteomics analytical workflow allowed to discover several novel potential cancer biomarkers in serum/plasma for clinical application (reviewed by [ 15 ]): for instance, recently, altered protein abundances were found in non-Hodgkin lymphoma, infected or not by human immunodeficiency virus, (i.e., C1Q and B2M) [ 34 ]; predicted the outcome of breast cancer patients receiving neodiuvant chemotherapy (APOC3, MBL2, ENG and P4HB) [ 35 ] or associated with high risk of ovarian cancer in BRCA1/2 carriers (SPARC and THBS1) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In label-free LC-MS/MS approaches, the relative abundance of different proteins is measured from mass spectral peak intensities or by spectral counting [ 17 ], and protein expression patterns can be compared across samples. Using this approach has enabled the discovery of numerous potential biomarkers (e.g., [ 18 , 19 , 20 ]). In the present work, label-free LC-MS/MS was used to identify circulating biomarkers capable of predicting relapse in a case/control study on 42 children with HL treated according to the European Network for Pediatric Hodgkin Lymphoma (EuroNet-PHL) C2 protocol (NCT02684708).…”
Section: Introductionmentioning
confidence: 99%
“…The normalized quantitative values of the remaining proteins except for the four proteins were derived by dividing the raw protein quantitative values in each sample by the NSF. The details of this method are described in previous studies [ 66 , 67 , 68 ].…”
Section: Methodsmentioning
confidence: 99%